CONTAMINATION OF MAFIC MAGMA BY PARTIAL MELTING OF DOLOMITIC XENOLITHS - Wenzel T.; Baumgartner L.P.; Brügmann G.E.; Konnikov E.G.; Kislov E.V.; Orsoev D.A. (My University, 2001)
Mg-skarns enclosed in dunite cumulates of the Neo-Proterozoic Ioko-Dovyren intrusion (northern Baikal region, Russia) can be traced to silica-poor dolomitic host rock layers. The dominant minerals of the skarns are brucite (pseudomorph after periclase), forsterite and Cr-poor spinel. Rapid heating of quartz-poor dolomitic xenoliths led to the formation of minor olivine, followed by the breakdown of dolomite to calcite and periclase. Xenoliths were partially melted upon further heating resulting in a calcite melt. This low-density melt was quantitatively squeezed out, mixed with the surrounding mafic magma and left behind periclase and olivine. This caused the crystallization of new olivine with elevated CaO contents in zones above skarn-bearing horizons. Mixing of calcite melt with the surrounding mafic magma also resulted in the crystallization of Cats-rich clinopyroxene instead of plagioclase. The mineralogy of contaminated dunite cumulates is consistent with assimilation of approximately 4wt% CaO by the Ioko-Dovyren mafic magma.
Keywords: Neoproterozoic; dunite cumulates; Baikal region; Russia; Precambrian::Proterozoic::Neoproterozoic; Докембрий::Протерозой::Неопротерозойская